Abnormal electrocaloric effect near ambient temperature in MgO modified NBT-KBT. (March 2022) - Kaur, Shubhpreet; Arora, Mehak; Kumar, Sunil; Malhi, Parambir Singh; Singh, Mandeep; Singh, Anupinder
Abstract: Present work proposes the advancement in the field of modern refrigeration based upon electrocaloric effect. The values of electrocaloric effect near ambient temperature is demonstrated in (Na0.41 K0.09 Bi0.50 )(Ti1- x Mgx )O3 where x = 0, 0.025 and 0.050. The MgO modified NBT-KBT sold solution has exhibited abnormal electrocaloric effect with ΔT − 2.03 K and electrocaloric strength ΔT/ΔE = 0.033 K cm kV −1 at 60 °C for highest doping. Moreover, a broad operating time range Tspan = 50–80 °C has achieved which allow this material to be useful for potential cooling application and provide new horizons in this field. Graphical Abstract: ga1 Highlights: Present work proposes the calculation of electrocaloric effect using Maxwell relations. Abnormal electrocaloric effect has been investigated in MgO modified NBT-KBT. A broad range of operating temperature for stable cooling application has been achieved.